Action analysis for animators - Webster, Chris, 1954- (Focal Press, 2012)
Action Analysis is one of the fundamental princples of animation that underpins all types of animation: 2d, 3d, computer animation, stop motion, etc. This is a fundamental skill that all animators need to create polished, believable animation. An example of Action Analysis would be Shrek's swagger in the film, Shrek. The animators clearly understood (through action analysis) the type of walk achieved by a large and heavy individual (the real) and then applied their observations to the animated character of an ogre (the fantastic). It is action analysis that enabled the animation team to visually translate a real life situation into an ogre's walk, achieving such fantastic results. Key animation skills are demonstrated with in-depth illustrations, photographs and live action footage filmed with high speed cameras. Detailed Case Studies and practical assignments ground action analysis methodology with real life examples. Action Analysis for Animators is a essential guide for students, amateurs and professionals. * A title that unites classic principles of Action Analysis with contemporary workflows. Apply the practices of action analysis to any animaton process. * Extensive illustrations of people and animals in motion that break down the action of animals and humans in a step-by-step manner. * Tips included throughout the book on how to capture motion and analyse action. * Detailed case studies illustrated with line drawings, diagrams, photographs and live action footage, integrate real world examples with practical knowledge. * Website included as a resource for amateur and experience animators, featuring Short Animations and Live Action examples juxtaposed with stills of animals and humans in motion.